Radicals: Resistance and Protest in Colonial Malaya, by Syed Muhd Khairudin Aljunied. NIU Press, 2015, 228 pp. - Mahani Musa, (Kajian Malaysia, 2017)
Writings on the radical movement in Malaya are nothing new among historians or postgraduate students at the MA or PhD levels even though these radicals have never been acknowledged by the government. Syed Muhd Khairudin's Radicals: Resistance and Protest in Colonial Malaya provides a new view on an old story. The writer begins his story with the demolition of the Pudu Prison on the night of 21 June 2010, which he sees as the end of one physical reminder of political prisoners interned there for the crime of fighting for their country's independence. From this event Syed Muhd Khairudin takes the readers to recall the chronology in the struggles of the Malay radicals, its ups and downs, from the Kesatuan Melayu Muda period until the Angkatan Sasterawan 50 era, the Malay Youth Congress and after the 1955 elections. Unlike earlier writings, Syed Muhd Khairudin's book scrutinises the mobilising concepts (which include ideas, visions and notions) used by the Malay radicals to organise, strategise and to consolidate their movement to achieve independence for Malaya.